2022
DOI: 10.1177/03010066221096987
|View full text |Cite
|
Sign up to set email alerts
|

The pairs training effect in unfamiliar face matching

Abstract: A wealth of studies have shown that humans are remarkably poor at determining whether two face images show the same person or not (face matching). Given the prevalence of photo-ID, and the fact that people employed to check photo-ID are typically unfamiliar with the person pictured, there is a need to improve unfamiliar face matching accuracy. One method of improvement is to have participants complete the task in a pair, which results in subsequent improvements in the low performer (“the pairs training effect”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…Similarly, in Study 2, we found no obvious differences in the content of super‐recognizer and control descriptions despite differences in the mean accuracy of their descriptions. This extends work by Ritchie et al ( 2022 ) who found no relationship between facial features discussed and the accuracy of dyads on a face‐matching task when both images were in view simultaneously. In the context of face communication specifically, Kramer and Gous ( 2020 ) found that discussion of the eyes, nose, mouth, hair, ears and face shape were not associated with identification accuracy.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similarly, in Study 2, we found no obvious differences in the content of super‐recognizer and control descriptions despite differences in the mean accuracy of their descriptions. This extends work by Ritchie et al ( 2022 ) who found no relationship between facial features discussed and the accuracy of dyads on a face‐matching task when both images were in view simultaneously. In the context of face communication specifically, Kramer and Gous ( 2020 ) found that discussion of the eyes, nose, mouth, hair, ears and face shape were not associated with identification accuracy.…”
Section: Discussionsupporting
confidence: 88%
“…This finding suggests that individuals with strong abilities in matching faces can communicate the basis for their decisions effectively and raises the possibility that they are also better able to describe faces. However, the content of participant discussions leading to this communication benefit is not well understood (Ritchie et al, 2022 ). Additionally, facial forensic examiners are known to outperform standard participant groups in face identification ability, and unlike other high‐performers in face identification (i.e., super‐recognizers), they are required to support face identification decisions with verbal justifications and specialized face vocabulary (White et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…In line with Dowsett and Burton (2015) and Ritchie et al (2022), the data were then split by performance in the pair (high performer, low performer) to test whether the pairs advantage was driven by improvements in the lower performer. Participants were defined as high and low performers based on their accuracy (percentage correct) at T1.…”
Section: Resultsmentioning
confidence: 99%
“…However, these main effects were qualified by a significant Pair Member × Experimental Session interaction, F (2, 184) = 11.19, p < .001, η p 2 = .11, BF 10 > 100. In order to break down the interaction and test our hypothesis that, as in Ritchie et al (2022), pairs training would predominantly affect the performance of the low performer in each pair, follow up one‐way ANOVAs were conducted for the high and low performers separately.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation